Reward Dependent Invigoration Relates to Theta Oscillations and Is Predicted by Dopaminergic Midbrain Integrity in Healthy Elderly - Steiger, Tineke K.; Bunzeck, Nico (Frontiers in Aging Neuroscience, 2017)
Motivation can have invigorating effects on behavior via dopaminergic neuromodulation. While this relationship has mainly been established in theoretical models and studies in younger subjects, the impact of structural declines of the dopaminergic system during healthy aging remains unclear. To investigate this issue, we used EEG in healthy young and elderly humans in a reward-learning paradigm. Specifically, scene images were initially encoded by combining them with cues predicting monetary reward (high vs. low reward). Subsequently, recognition memory for the scenes was tested. As a main finding, we can show that response times during encoding were faster for high reward predicting images in the young but not elderly participants. This pattern has resembled in power changes in the theta-band (4-7 Hz). Importantly, analyses of structural MRI data revealed that individual reward-related differences in the elderlies’ response time could be predicted by the structural integrity of the dopaminergic substantia nigra (as measured by magnetization transfer). These findings suggest a close relationship between reward-based invigoration, theta oscillations and age-dependent changes of the dopaminergic system.